Efektivitas Penyelesaian Hukum Akibat Sound Horeg Melalui Restoratif Justice - Parikesit, Dhana Harliza Putri; Romadhon, Ahmad Heru; Gunawan, Bambang Panji (Legal Standing : Jurnal Ilmu Hukum, 2025)
This research aims to examine the effectivenessof legal settlements regarding the nouise disrtubances caused by sound horeg through  a restorative justice approach . sound horeg refers to high-decibel audio devices used in community events such as birthdays, circumcisions, and carnivals. Excessive and unregulated use of these devices often disturbs public comfort and order. This can be considered an unlawful act, as it violates established noise level thresholds and infringes on the public’s right to a peaceful and healthy environment. The research adopts a normative juridical method with statutory and conceptual approaches. Data sources include literature review of relevant regulations such as the Criminal Code, Law No. 32 of 2009 on Environmental Protection and Management, and Ministerial Regulations on noise level standards. Secondary data were obtained from articles, news reports, community complaints, and scientific journals. The findings show that a restorative justice approach is more effective in resolving legal issues related to sound horeg compared to repressive methods. Restorative justice emphasizes deliberation, restoration of social relations, education for offenders, and continuous supervision. This approach helps minimize social conflict, enhances legal awareness in the community, and supports the creation of sustainable public order.